CASE STUDY OF DAMAGE ANALYSIS OF HT BEND PULLEY ON OLC4A COAL CONVEYOR PT BUKIT ASAM TBK: - - Atos, Praja Dilla (Journal of Mechanical Science and Engineering, 2023)
HT (High Tension) bend pulley is one of the components in the conveyor system which functions to redirect the conveyor belt and provide tension on the conveyor belt when there is a bend in a conveyor belt system. The HT bend pulley on the OLC4A conveyor line at PT Bukit Asam Tbk (PTBA) has been damaged and after an investigation into the damage, it is known that on the right side of the HT bend pulley there is a broken shaft. This damage also has an impact on damage to other machine component components that are around the HT bend pulley such as bearings, surrounding construction. Visual inspection is carried out by taking pictures of damaged shaft parts and analyzing the shape of the shaft fracture. Material identification is used to determine the strength of the material, namely the strength to withstand the tension that occurs on the shaft. The inspection results show that there is crack initiation. This failure mode assumes that the shaft is subjected to rotational loads which causes the tensile stress to exceed its ultimate strength and on the surface of the shaft there are also traces of rewelding which may be aimed at the hard-facing process on the surface of the shaft. The hard-facing welding process will affect changes in the microstructure and the hardness value of the pulley shaft. Judging from the shape of the shaft fracture, brittle fracture occurred on the left side and ductile fracture on the right side of the shaft. It is possible that a crack had occurred at that point before the shaft fracture occurred, and the condition of the broken shaft pulley has been hard faced (repaired). The C45 Steel shaft material can be equivalent to P265GH although the P265GH material tends to have lower specifications than C45 Steel. For certain operating conditions it is better to stick to the original material, namely C45 Steel.